DEVELOPMENT OF SELF-REGULATED LEARNING IN THE PROJECT-BASED HYBRID LEARNING MODEL TO IMPROVE SELF-REGULATED LEARNING - Priyambudi, Surya; Setyowati, Yulis; Grahani, Firsty Oktaria (JURNAL KONFIKS, 2024)
In the current independent learning curriculum of the independent campus, learning in Higher Education has shifted to being based on internet digitalization. SPADA, which will be developed, is an application owned by Wijaya Putra University, which is located at spada.uwp.ac.id. The combination of project-based learning that implements hybrid learning is learning simultaneously online and offline. The problem formulation is formulated: How is the feasibility of developing a project-based hybrid learning model based on the SPADA application for student learning? How can the project-based hybrid learning model based on the SPADA application improve students' self-regulated learning abilities? This study aims To produce the feasibility of developing a project-based hybrid learning model based on the SPADA application for student learning and To explain the project-based hybrid learning model based on SPADA in improving students' self-regulated learning abilities. The research method uses an experimental approach with pretest and posttest. Based on the research results, the project-based hybrid learning model based on the SPADA application to improve the self-regulated learning abilities of Wijaya Putra University students is very effective. This is because the self-regulated learning ability for the goal-setting indicator has increased by 0.98, the environment setting indicator has increased by 0.90, the task strategy indicator has increased by 1.06, the time management indicator has increased by 1.32, the help-seeking indicator has increased by 1.81, and for the self-evaluation indicator has increased by 1.14. The implications of the findings in this study reinforce that knowledge and skills in self-regulated learning abilities are very much needed to support educational models and processes that are increasingly disrupting traditional methods by knowing the selection of digital learning resources and can encourage efforts to improve abilities in self-regulated learning abilities.